(untitled) (Proceedings of Faculty of Civil Engineering, 2022)
The paper presents research conducted as part of the ZIP UNIRI scientific project “Investigation of the behaviour of composite panel components with integrated steel core”. The aim of the scientific project is to better understand the behaviour of the components of the innovative structural panel system in order to investigate the potential of its application in construction.